Impact of the COVID-19 pandemic on the utilisation of health services at public hospitals in Yemen: a retrospective comparative study. Issue 1 (3rd January 2022) - Kotiso, Mikyias; Qirbi, Naseeb; Al-Shabi, Kahtan; Vuolo, Elena; Al-Waleedi, Ali; Naiene, Jeremias; Senga, Mikiko; Khalil, Mohammed; Basaleem, Huda; Alhidary, Ahmed
Abstract : Background: The COVID-19 pandemic has led to a global crisis, creating an unprecedented situation, which has taken the world by storm, overshadowing on all life' aspects and having a significant impact on the health systems of most countries. In this study, the delivery of health services is investigated both before and during the outbreak of the COVID-19 pandemic at public hospitals in Yemen to assess the impact of COVID-19 on the utilisation of health services. Method: Data collected from 127 hospitals in Yemen were reviewed using the DHIS2 system. The data represented 3 months before the outbreak of COVID-19 between January and March 2020 and during the outbreak of COVID-19 outbreak between April and June 2020. The results were then compared with the same period in 2019. The utilisation pattern of healthcare services during the period of investigation was compiled and analysed by applying a generalised estimating equation (GEE) to examine the effects of the COVID-19 outbreak in Yemen. The data collected from the targeted hospitals included information related to consultations, surgeries, deliveries, C-sections and penta-3rd dose immunisation. Results: The trendline of health services used during the pandemic showed a gradual decline beginning from April 2020 for consultations, surgeries and penta-3rd dose utilisation. The GEE model revealed a significant effect (p<0.05) during the outbreak compared with preoutbreak in the consultation services (B=−1, 343.9; 95% CI −1, 767.2 to −920.6; χ 2 =38.718), surgeries (B=−54.98; 95% CI −79.13 to −30.83, χ 2 =19.911) and penta-3rd dose (B=−24.47; 95% CI −30.56 to −18.38 and χ 2 =62.010). As for deliveries and C-sections, the results were shown to be statistically non-significant. Conclusion: The impact of COVID-19 on continuity of health services delivery in Yemen has been distinct and profound, where the study revealed that the number of the consultations, surgeries and number of vaccinated children have been declined during the COVID-19 pandemic, likely due to the partially lockdown measures taken and fear of being infected. However, the deliveries and C-section services remained nearly in the same level and did not affect by the COVID-19 pandemic.